2012
DOI: 10.3109/08958378.2011.633281
|View full text |Cite
|
Sign up to set email alerts
|

Effects on airways of short-term exposure to two kinds of wood smoke in a chamber study of healthy humans

Abstract: The results indicate that relatively low levels of wood smoke exposure induce effects on airways. Effects on airway epithelial permeability was shown for the start-up phase of wood burning, while FENO increased after the burn-out session. CC16 seems to be a sensitive marker of effects of air pollution both in serum and urine, but its function and the significance need to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 67 publications
7
53
2
Order By: Relevance
“…Toxicological effects related to human health Human controlled exposure studies report that short-term inhalation of woodsmoke induces mild inflammatory effects including distal airway inflammation, increased oxidative stress and immune cell recruitment, but no effects on measures of lung function [98][99][100][101][102][103]. Studies also report systemic effects such as increased levels of coagulation markers, and decreased heart rate variability and systemic inflammation [100,[104][105][106][107].…”
Section: Toxicity Of Woodsmoke Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicological effects related to human health Human controlled exposure studies report that short-term inhalation of woodsmoke induces mild inflammatory effects including distal airway inflammation, increased oxidative stress and immune cell recruitment, but no effects on measures of lung function [98][99][100][101][102][103]. Studies also report systemic effects such as increased levels of coagulation markers, and decreased heart rate variability and systemic inflammation [100,[104][105][106][107].…”
Section: Toxicity Of Woodsmoke Particlesmentioning
confidence: 99%
“…This ambiguity could partly be due to the great heterogeneity in experimental set-ups, fuel type, biomass exposure generation and physicochemical properties of PM. Interestingly, the two studies reporting significant effects for either respiratory or cardiovascular end-points applied biomass PM originating from flaming combustion of wood logs in conventional stoves, rendering emissions of soot and organics [98,99,104,105]. Other studies applied PM from more complete or more incomplete (smouldering) combustion conditions.…”
Section: Toxicity Of Woodsmoke Particlesmentioning
confidence: 99%
“…(12) Recent controlled human wood smoke exposure studies have provided additional insights into the airway oxidative, inflammatory and systemic effects. (13)(14)(15)(16) Since the combustion conditions for biomass burning can vary substantially in terms of fuel type, air supply, temperature, and category of stoves and boilers, the physico-chemical characteristics of the wood smoke PM also show large differences. (17) Not surprisingly, systematic research with in vitro models performed by various research groups has resulted in considerably different toxicological capacity and mechanisms for biomass combustion PM.…”
Section: Introductionmentioning
confidence: 99%
“…When effects of total PM with organic extracts of the PM and washed particles were compared, the response induced by the organic fraction was not linked to the content of PAHs, suggesting that other organic components (e.g., quinone-like compounds) were involved . Studies that examined effects of combustion cycle phase have shown differences in response at the startup versus the burn-out phase (Stockfelt et al, 2012); there are differences in the organic chemical makeup between these two phases.…”
Section: Toxicology Of Wood Smokementioning
confidence: 99%